Online New Student Registration System for SMA Negeri 1 Ketaggungan Brebes Using the CodeIgniter Framework - Ahmad Taufiq; Nurul Bahiyah (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2021)
New student registration system manually is still used by some schools in Indonesia. But the problem is that prospective students are still many who feel difficulty with the system of the manual registration and of course they need registration system which more quick and efficient. Moreover, the conditions of the pandemic at this time, where there are rules to keep the protocol of the Health. Such as keeping physical distancing and limiting public service. The research method used in this research is the design and manufacture of the system, namely to design web-based system of a new student registration that can be accessed through a web browser. The online registration system of new students is built with PHP programming language and utilizing a MySQL database as a database server, and using the Codeigniter Framework. The result of this research is the web-based online registration system of new students already have the ability to provide convenience for prospective students to obtain all the information about the acceptance of new students and do the online registration process.